Pembuatan VCO (Virgin Coconut Oil) sebagai Pengolahan Buah Kelapa dengan Metode Pendiaman - Mujuna Hatuala; Veni Rosnawati; La Ali (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Virgin Coconut Oil (VCO) is a processed coconut product with high economic and health value. VCO production is known to be relatively easy, inexpensive, and capable of producing high-quality oil rich in benefits, including as a traditional medicine and natural ingredient for beauty and health. This community service activity aims to provide students of the Biology Education Study Program at Buton Muslim University with an understanding and practical skills regarding the VCO production process as a form of utilization of local natural resources, especially coconuts. The methods used in this activity include lectures or delivery of theoretical material, interactive discussions on the content and benefits of VCO, and direct practice in making virgin coconut oil using the settling method. This method was chosen because it does not require complicated equipment, does not use excessive heating, and is able to maintain the natural quality of the resulting oil. During the implementation, students are invited to observe and follow the entire process, from selecting good coconut raw materials, the grating process, squeezing coconut milk, natural fermentation through settling, to the process of separating oil from sediment and filtering. The results of this activity demonstrated that students not only understood the concept and theory of VCO production but also produced 1,500 ml of virgin coconut oil packaged in five 300 ml bottles. The VCO was then sold to the public for approximately Rp 30,000 per bottle. Through this activity, students not only gained contextual learning experiences but also developed insights into sustainable, locally-based entrepreneurship.